2020
DOI: 10.3390/app10217818
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Local Structure Change during the Photoabsorption Processes of Photocatalysts by the Ultrafast Pump-Probe XAFS Method

Abstract: The birth of synchrotron radiation (SR) facilities and X-ray free electron lasers (XFELs) has led to the development of new characterization tools that use X-rays and opened frontiers in science and technology. Ultrafast X-ray absorption fine structure (XAFS) spectroscopy for photocatalysts is one such significant research technique. Although carrier behavior in photocatalysts has been discussed in terms of the band theory and their energy levels in reciprocal space (k-space) based on optical spectroscopic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…Its inherent advantages, including short time scanning periods, low radiation dose, information on kinetics, and the elucidation of chemical-reaction and phase-transition mechanisms, allow QEXAFS to play an important role in the field of time-resolved studies (Eslava et al, 2016;Prestipino et al, 2011;Gaur et al, 2019;Marchionni et al, 2020). Differing from the sophisticated setups of energy-dispersive XAFS (Flank et al, 1982) and pump-probe XAFS (Oyanagi et al, 2001;Bressler et al, 2009;Uemura et al, 2020;Smolentsev et al, 2018), the QEXAFS method can be developed on the general XAFS beamline and shares most of the devices with the conventional XAFS experimental method.…”
Section: Introductionmentioning
confidence: 99%
“…Its inherent advantages, including short time scanning periods, low radiation dose, information on kinetics, and the elucidation of chemical-reaction and phase-transition mechanisms, allow QEXAFS to play an important role in the field of time-resolved studies (Eslava et al, 2016;Prestipino et al, 2011;Gaur et al, 2019;Marchionni et al, 2020). Differing from the sophisticated setups of energy-dispersive XAFS (Flank et al, 1982) and pump-probe XAFS (Oyanagi et al, 2001;Bressler et al, 2009;Uemura et al, 2020;Smolentsev et al, 2018), the QEXAFS method can be developed on the general XAFS beamline and shares most of the devices with the conventional XAFS experimental method.…”
Section: Introductionmentioning
confidence: 99%
“…However, the EDXAS setup does not allow for measurements of the fluorescence signal in samples, and it requires a very flat sample surface. Pump-probe XAS can only be used for samples that can be excited by pulse laser, such as photocatalysts (Uemura et al, 2020;Smolentsev et al, 2018). The QXAFS technique can be more flexible and convenient for in situ/operando XAFS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[3] We have acquired PP X-ray absorption near edge structure (PP-XANES) spectra of WO 3 after pulsed laser irradiation and have found that the MS was created within 150 ps, followed by relaxation to the ground state (GS) with a time constant of 2 ns. [4][5][6][7] We proposed that the photoelectrons were trapped at distorted stoichiometric W sites in the crystal lattice, similar to the trapping of polarons, instead of at surface or bulk defects. [6] The formation time for the MS, 150 ps, was longer than that for the other oxides such as TiO 2 and Fe 2 O 3 , consistent with previouslyreported optical measurement results [8].…”
mentioning
confidence: 99%